Wolfram Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Two unrelated patients with Wolfram syndrome (diabetes insipidus, diabetes mellitus, optic atrophy, and deafness) in whom MRIs of the brain provide evidence of a diffuse neurodegenerative process are reported from the Departments of Neurology and Ophthalmology, University of California at San Francisco, CA.